Corporate Governance and Corporate Social Responsibility Disclosures: Evidence from an Emerging Economy - Khan, Arifur (Journal of business ethics, 2013)
We examine the relationship between corporate governance and the extent of corporate social responsibility (CSR) disclosures in the annual reports of Bangladeshi companies. A legitimacy theory framework is adopted to understand the extent to which corporate governance characteristics, such as managerial ownership, public ownership, foreign ownership, board independence, CEO duality and presence of audit committee influence organisational response to various stakeholder groups. Our results suggest that although CSR disclosures generally have a negative association with managerial ownership, such relationship becomes significant and positive for export-oriented industries. We also find public ownership, foreign ownership, board independence and presence of audit committee to have positive significant impacts on CSR disclosures. However, we fail to find any significant impact of CEO duality. Thus, our results suggest that pressures exerted by external stakeholder groups and corporate governance mechanisms involving independent outsiders may allay some concerns relating to family influence on CSR disclosure practices. Overall, our study implies that corporate governance attributes play a vital role in ensuring organisational legitimacy through CSR disclosures. The findings of our study should be of interest to regulators and policy makers in countries which share similar corporate ownership and regulatory structures.